Focus on Disruptive Mood Dysregulation Disorder: A review of the literature. (September 2019) - Bruno, Antonio; Celebre, Laura; Torre, Giovanna; Pandolfo, Gianluca; Mento, Carmela; Cedro, Clemente; Zoccali, Rocco A.; Muscatello, Maria Rosaria Anna
Highlights: Disruptive Mood Dysregulation Disorder (DMDD) is a new diagnosis of the DSM-5. DMDD is characterized by a persistently negative mood and severe temper outbursts. Since DMDD is a new diagnosis, there are not enough published validity studies. DMDD' prevalence, epidemiology, risk factors and treatment are still not clarified. Abstract: The inclusion of the Disruptive Mood Dysregulation Disorder (DMDD) in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), under the category of depressive disorders, provides a diagnosis for those children and adolescents with severe persistent irritability and temper outbursts, once misdiagnosed as Bipolar Disorders. The main and constantly present features of DMDD are chronic, non-episodic and persistent irritability, and temper tantrums disproportionate with the trigger. DMDD is characterized by high rates of comorbidity with other psychiatric disorders. Its main clinical manifestations overlap with Oppositional Defiant Disorder, Conduct Disorder, and Attention-Deficit/Hyperactivity Disorder. For this diagnostic overlap and the increasing use of pharmacological treatments in children and adolescents, the inclusion of DMDD diagnosis has been subjected to many criticisms. Since it is a new diagnostic entity, literature on DMDD prevalence, epidemiology, risk factors, and treatment guidelines, is still sparse and unclear. The aim of this review is to collect and analyze the literature on DMDD diagnostic criteria and main hallmarks, with particular attention to comorbidities and treatment options.